Comparison of Atherogenic Index of Plasma (AIP) Between Postmenopausal Women with Central Obesity and Postmenopausal Nonobese Women - Khanam, Monowara; Khan, Md Aminul Haque; Rahman, Md Rewanur; Parvin, Rukhsana; Akhter, Selima; Ferdousi, Shahnila (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2014)
Background: Following menopause there are changes in values of lipid profile parameters. Abdominal obesity has also been linked to significant metabolic abnormalities including changes in lipid parameter values. Atherogenic index of plasma (AIP) calculated as log (TG/HDL-C) has been used as some practitioners as a significant predictor of atherosclerosis. So, we designed this study to observe the pattern of lipid profile parameters and to find out AIP in postmenopausal central obese women and to compare these between postmenopausal women with central obesity and postmenopausal nonobese women. Objectives: To assess the lipid profile status and AIP of postmenopausal women with central obesity and to compare these parameters with that of postmenopausal nonobese women. Materials & Methods: This cross sectional study was carried out in the department of Biochemistry, Bangabandhu Sheikh Mujib Medical University, Dhaka, Bangladesh. Sixty six postmenopausal women with central obesity and age matched 56 nonobese postmenopausal women were included in the study. Central obesity was defined having waist hip ratio more than 0.8 and BMI <25.0. All statistical analyses were done by SPSS 18.0. p values <0.05 were considered significant. Results: Statistically no significant difference was observed between the central obese women and nonobese women in lipid profile parameters. But AIP was found significantly higher in postmenopausal central obese women. Conclusion: Central obese postmenopausal women may be at higher risk of cardiovascular events compared with postmenopausal nonobese women in spite of no difference in lipid profile parameters as their AIP values are significantly different. DOI: http://dx.doi.org/10.3329/cmoshmcj.v13i2.21064